Modern Aspects of the Etiology of Acute Intestinal Infections (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents modern data on etiology of acute intestinal infections, their clinical manifestations, modern approaches to diagnosis and treatment. The questions of probiotic and metabolic therapy in acute intestinal infections are discussed.